2020
DOI: 10.1063/5.0003443
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental cupolets of chaotic systems

Abstract: Cupolets are a relatively new class of waveforms that represent highly accurate approximations to the unstable periodic orbits of chaotic systems, and large numbers can be efficiently generated via a control method where small kicks are applied along intersections with a control plane. Cupolets exhibit the interesting property that a given set of controls, periodically repeated, will drive the associated chaotic system onto a uniquely defined cupolet regardless of the system’s initial state. We have previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…During the course of the targeting work, it became apparent that a transition sequence could be made to close up on itself and produce a closed loop around the attractor [71]. By interlacing the control sequences of the cupolets used in the transition sequence, the new orbit was seen to be a cupolet that had been created separately from the control method and was instead constructed by amalgamating the orbits of existing simpler cupolets.…”
Section: Fundamental Cupoletsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the course of the targeting work, it became apparent that a transition sequence could be made to close up on itself and produce a closed loop around the attractor [71]. By interlacing the control sequences of the cupolets used in the transition sequence, the new orbit was seen to be a cupolet that had been created separately from the control method and was instead constructed by amalgamating the orbits of existing simpler cupolets.…”
Section: Fundamental Cupoletsmentioning
confidence: 99%
“…These observations inspired the development of a new irreducibility property that distinguishes the cupolets whose orbits can be decomposed by sequences of switchable cupolets from those cupolets whose orbits cannot be broken down in this manner [71]. Cupolets for which no decomposing set of cupolets can be found are said to be irreducible with respect to a working library of cupolets and are called fundamental cupolets.…”
Section: Fundamental Cupoletsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed methods of graph theory to be brought to bear to develop an algorithm to calculate an efficient, in some sense, low-energy transition from an initial trajectory to a target trajectory by riding along and transitioning between cupolets [12]. Further investigation revealed that certain cupolets could be defined as fundamental and others as composite, with the fundamental cupolets irreducible within a finite space of cupolets [13].…”
Section: Introductionmentioning
confidence: 99%